2010
DOI: 10.1002/syn.20768
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal epigenetic modification at the doublecortin gene is involved in the impairment of neurogenesis with aging

Abstract: Recent research has suggested that epigenetic mechanisms, which exert lasting control over gene expression without altering the genetic code, could mediate stable changes in brain function. A growing body of evidence supports the idea that epigenetic changes play a role in the etiology of aging and its associated brain dysfunction. The present study was undertaken to evaluate the age-related changes in the expression of doublecortin, which is a marker for neuronal precursors, along with epigenetic modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…These modifiable environmental interventions increase brain and serum BDNF levels[43][46]. Aerobic exercise for example induces both short-term and longer-term increases in circulating BDNF levels, in parallel with improvements in memory performance[47].…”
Section: Discussionmentioning
confidence: 99%
“…These modifiable environmental interventions increase brain and serum BDNF levels[43][46]. Aerobic exercise for example induces both short-term and longer-term increases in circulating BDNF levels, in parallel with improvements in memory performance[47].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased hippocampal neurogenesis is proposed as an important mechanism underlying age‐related cognitive decline as well as neurodegenerative disorders such as AD and various types of dementia (Kuzumaki et al, ). Evidence in this regard was recently published in two separate recent studies examining hippocampal neurogenesis in human tissue from people suffering mild cognitive impairment and AD.…”
Section: Hippocampal Neurogenesis During the Developmentally Criticalmentioning
confidence: 99%
“…Increasing evidence has shown that epigenetic mechanisms are involved in regulating aging-related cellular behaviors. 29,30 It is proposed that the epigenetic modulated switch of microglia polarization is influenced by aging. Indeed, by comparing the mRNA levels of those markers and related molecules in aged mice (16-18 months old) with young mice (2-3 months old), we showed that the M1 markers such as iNOS, TNF-a and IL-6 were generally increased in aged mice, whereas the M2 markers including Arginase1, CD206 and IGF-I were expressed at lower levels (Figures 7a and b).…”
Section: Da Neurons In the Sncmentioning
confidence: 99%